2020
DOI: 10.1097/sih.0000000000000453
|View full text |Cite
|
Sign up to set email alerts
|

Do Gender-Based Disparities in Authorship and Editorship Exist in Healthcare Simulation Journals? A Bibliometric Review of the Research

Abstract: Publication in peer-reviewed journals, and serving on editorial boards, is considered an indicator of academic productivity and success, and a means of influencing discourse and practice in a field. This bibliometric review explored gender in authorship, and editorship, across the 3 existing English language, nonspecialty specific healthcare simulation journals. In total, 40.4% of publications had women first authors and 34.4% had women senior authors. There were no differences by journal and no apparent chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…Persistent issues include poor support of women, gender stereotypes, sexism and bias in funding awards 19 . Action by both men and women is important; for example, we identified a significant tendency for women first authors and last authors to publish together, reflecting the greater likelihood of a mentor‐mentee relationship among same sex authors that has been identified previously in other specialties 17,25,43 . Although a personal preference for gender concordance may exist, 17 whereby junior and senior women researchers ‘seek out one another’, 43 given the predominance of men in senior roles in academic medicine ‘crossing the gender line’ in mentoring could be imperative for ensuring women's success 17 .…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Persistent issues include poor support of women, gender stereotypes, sexism and bias in funding awards 19 . Action by both men and women is important; for example, we identified a significant tendency for women first authors and last authors to publish together, reflecting the greater likelihood of a mentor‐mentee relationship among same sex authors that has been identified previously in other specialties 17,25,43 . Although a personal preference for gender concordance may exist, 17 whereby junior and senior women researchers ‘seek out one another’, 43 given the predominance of men in senior roles in academic medicine ‘crossing the gender line’ in mentoring could be imperative for ensuring women's success 17 .…”
Section: Discussionmentioning
confidence: 78%
“…Although Editor‐in‐Chiefs in 2019 were predominantly men, at least in the small sample of journals we considered, our analysis of editorship overall found that women were only slightly less frequently represented (42.1%) on editorial boards overall than men and that statistically equal numbers between men and women were achieved in three of the four journals examined. These data are more favourable than observed in the editorial board membership of many medical specialties 19,22,25,26 where under‐representation of women on editorial boards has been referred to as a ‘macro‐inequality’ 38 and has been clearly documented for over two decades 39 . Membership on editorial boards is a notable achievement, and provides a unique networking opportunity 40 .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations